THU0121 Bcl-xl and plasma cell survival in rheumatoid synovium. (1st June 2001) - Busteed, S; Bennett, MW; Stone, M; Molloy, C; O'Connell, J; Shanahan, F; Molloy, MG
Abstract : Background: Bcl-xL is a Bcl-2 homologue that regulates lymphocyte apoptosis. It has been reported that co-culture of B cells with rheumatoid synovial stromal cells induces upregulation of Bcl-xL, consequently inhibiting B cell apoptosis. Impaired apoptosis of auto-antibody producing B cells may contribute to the perpetuation of inflammation in rheumatoid arthritis (RA). The phenotype of synovial T lymphocytes in RA – Bcl-xL high /Bcl-2 low, may also be linked to the enhanced survival of T lymphocytes within the joint. Objectives: In this study, we examined the expression of Bcl-xL in rheumatoid synovium using immunohistochemistry. Methods: Sections of synovium were obtained intraoperatively from patients with RA (n = 18). Specimens from patients with osteoarthritis were used as non-inflammatory controls (n = 9). Staining was carried out using a polyclonal rabbit antibody to Bcl-xL. Peripheral blood lymphocytes were used as positive biological controls. Detection of cell death was carried out using the TUNEL assay (terminal deoxynucleotidyl transferase (TdT) mediated dUTP nick end labelling). Identification of plasma cells within the lymphocyte population was performed using a monoclonal antibody to CD138. Results: Bcl-xL was expressed in both RA and OA tissue. Of note, there was a marked infiltrate of Bcl-xL positive cells in 13 of the 18 RA sections with scattered positive cells in a further 2 sections. Only 1 of the 9 OA sections demonstrated a similar degree of plasma cell infiltration and Bcl-xL expression, although a few positive plasma cells were noted in the remaining sections. Plasma cells infiltrates that were Bcl-xL positive were noted to be TUNEL-negative on consecutive sections. Conclusion: Upregulation of Bcl-xL by plasma cells in rheumatoid synovium may prevent their elimination by apoptosis and may play a role in the pathogenesis in rheumatoid arthritis.